Graphene Oxide-Hybridized Waterborne Epoxy Coating for Simultaneous Anticorrosive and Antibiofilm Functions - Zhou, Ying; Wang, Haoran; Zhang, Cheng; Zhou, Qixin; Rodrigues, Debora F. (Frontiers in Materials, 2022)
Multifunctional coatings with simultaneous antibacterial and anticorrosive properties are essential for marine environments, oil & gas industry, medical settings, and domestic/public appliances to preserve integrity and functionality of pipes, instruments, and surfaces. In this work, we developed a simple and effective method to prepare graphene oxide (GO) hybridized waterborne epoxy (GOWE) coating to simultaneously improve anticorrosive and antibacterial properties. The effects of different GO filler ratios (0.05, 0.1, 0.5, 1 wt.%) on the electrochemical and antibacterial behaviors of the waterborne epoxy coating were investigated over short- and long-term periods. The electrochemical behavior was analyzed with salt solution for 64 days. The antibacterial effect of GOWE coating was evaluated with Shewanella oneidensis (MR-1), which is a microorganism that can be involved in corrosion. Our results revealed that concentrations as low as 0.5 wt.% of the GO was effective for superior anticorrosive and antibacterial performance than the waterborne epoxy coating without Graphene oxide. This result is due to the high hydrophilicity of the Graphene oxide fillers, which allowed great dispersion in the waterborne epoxy coating matrix. Furthermore, this study used a corrosion relevant bacterium as a model organism, i.e., Shewanella oneidensis (MR-1), which is more relevant for real word applications. This as-prepared GO-hybridized waterborne polymeric hybrid film provides new insight into the application of 2D nanomaterial polymer composites for simultaneous anticorrosive and antibacterial applications.